2016
DOI: 10.2147/dddt.s115099
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose modified-release prednisone in axial spondyloarthritis: 3-month efficacy and tolerability

Abstract: BackgroundOral glucocorticoids (GCs) have been shown to be effective in reducing the inflammatory symptoms of rheumatoid arthritis, but their use is not supported by evidence in spondyloarthritis (SpA). Modified-release (MR) oral prednisone taken at bedtime has been shown to be more effective than immediate-release prednisone taken in the morning. The efficacy of low-dose MR prednisolone in patients with SpA is unknown.Patients and methodsThis single-center cohort study retrospectively assessed the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The results showed a significant decrease in disease activity (from 5.5 ± 2.6 to 3.0 ± 2.8 on the BAS-DAI; p = 0.001), but not concerning mobility (BASMI) or enthesitis index (Maastricht Ankylosing Spondylitis Enthesitis Score -MASES). No serious adverse event was observed during the 12-week follow-up period [68] (2C). Another short-term randomized, placebocontrolled trial, which included 34 patients with AS, found that daily treatment with two oral doses of prednisolone (20 or 50 mg) for two weeks improved activity indices compared with the placebo.…”
Section: What Is the Evidence For The Use Of Glucocorticoids In Patiementioning
confidence: 89%
“…The results showed a significant decrease in disease activity (from 5.5 ± 2.6 to 3.0 ± 2.8 on the BAS-DAI; p = 0.001), but not concerning mobility (BASMI) or enthesitis index (Maastricht Ankylosing Spondylitis Enthesitis Score -MASES). No serious adverse event was observed during the 12-week follow-up period [68] (2C). Another short-term randomized, placebocontrolled trial, which included 34 patients with AS, found that daily treatment with two oral doses of prednisolone (20 or 50 mg) for two weeks improved activity indices compared with the placebo.…”
Section: What Is the Evidence For The Use Of Glucocorticoids In Patiementioning
confidence: 89%
“…It was shown that shortterm high dose GC use is beneficial to improve clinical symptom and signs. 39,40 Therefore, the phrase 'there is no evidence in use of systemic GCs in ax-SpA' was altered as 'long-term systemic GCs are not recommended', which is compatible with 2016 update of the ASAS/ EULAR Management Recommendations for ax-SpA. 4…”
Section: Recommendationmentioning
confidence: 98%